f-Block element separation mediated by carboxylated Fe3O4 nanoparticles as robust adsorbents in acidic systems - Dharmendra B. Sharma; Rutuja Gumathannavar; Arijit Sengupta; Atul Kulkarni (Scientific Reports)
Abstract Citric acid functionalized magnetic nanoparticles (CA-MNP) were synthesized and studied for sorption of two representative trivalent lanthanide and actinide ions (Eu3+ and Am3+). The material was characterized using various analytical techniques such as FTIR, SEM, TEM and zeta potential measurement etc. which indicated successful synthesis of magnetic nanoparticles and citric acid coating on its surface. The uptake study indicated efficient sorption of Eu3+ (76.7%) and Am3+ (60.9%) at optimum concentration of CA-MNP) 2.5 mg mL− 1. Sorption of metal ion onto the substrate was confirmed by EDXRF results. The sorption process indicated better kinetics for Eu3+ compared to previously reported studies and both the radionuclides were found to be following pseudo-second order rate kinetics. The rate constants were found to be 4.76 × 10− 9 mg g− 1 min− 1 and 2.45 × 10− 7 mg g− 1 min− 1 for Am3+ and Eu3+, respectively. Thermodynamic study indicated ΔG values as − 15.8 kJ mol− 1 and − 17.9 kJ mol− 1 for Am3+ and Eu3+, respectively indicating the spontaneity of the sorption processes. Stripping with different reagents viz. 0.1 M EDTA, 0.1 M oxalic acid, 0.1 M Na2CO3, and 0.1 M HNO3 indicated best results with 0.1 M EDTA. >99% of loaded Eu3+ is stripped in two stripping cycles while stripping of Am3+ requires more number of cycles to quantitatively strip the loaded radionuclide.